Clinical and epidemiological aspects of microcephaly in the state of Piauí, northeastern Brazil, 2015‐2016 - Isabel Marlúcia Lopes Moreira de Almeida; Carmen Viana Ramos; Danielle Carvalho Rodrigues; Amanda Carvalho de Sousa; Maria de Lourdes Cristina Alcântara Paz Carvalho do Nascimento; Marcos Vilhena Bittencourt da Silva; Francisca Miriane Araújo Batista; Jéssica Pereira dos Santos; Roselane Sampaio de Oliveira; Filipe Augusto de Freitas Soares; Samanta Cristina das Chagas Xavier; Filipe Anibal Carvalho‐Costa (Brazilian Society of Pediatrics, 2019)
Objectives: To describe aspects of the microcephaly epidemic in the state of Piauí. Methods: All cases of congenital microcephaly confirmed in the state between 2015 and 2016 were included (n = 100). Investigation forms of the Regional Reference Center for Microcephaly were reviewed. Discarded cases (n = 63) were used as a comparison group. Results: In October, November, and December 2015 incidence rates reached 4.46, 6.33 and 3.86/1000 live births, respectively; 44 cases were reported in the state capital. Among the mothers of confirmed and discarded cases, the frequency of skin rash during pregnancy was 50/97 (51.5%) and 8/51 (15.7%), respectively (p < 0.001); 33 confirmed cases (35.9%) had a head circumference z‐score between −2 and −3, 23 (25%) between −3 and −4, and 8 (8.7%) had a z‐score of less than −4. Head computer tomography scans revealed calcifications in 78/95 (82.1%) cases. Lissencephaly, hydrocephalus and agenesis of the corpus callosum were also frequently observed. Ophthalmic findings included retinal pigment epithelium rarefaction and atrophy. Absence of otoacoustic emissions was observed in 21/70 cases. One newborn also presented lower limb muscle atrophy. There were no significant differences in vaccination rates for influenza, diphtheria‐tetanus‐acellular pertussis, and hepatitis B in either group. Conclusions: The state of Piauí, like others in the northeastern region, faced an epidemic of congenital microcephaly between 2015 and 2016, presumably related to congenital Zika virus infection, more intense in the capital. Current challenges include the improvement of vector control, basic research, scaling‐up of diagnostic tools for pre‐natal screening of Zika virus, vaccines, and health care for affected children. Resumo: Objetivos: Descrever os aspectos da epidemia de microcefalia no Estado do Piauí. Métodos: Foram incluídos todos os casos de microcefalia congênita confirmados no estado entre 2015‐2016 (n = 100). Os formulários de investigação do Centro Regional de Referência em Microcefalia foram analisados. Os casos descartados (n = 63) foram usados como grupo de comparação. Resultados: Em outubro, novembro e dezembro de 2015, as taxas de incidência atingiram 4,46, 6,33 e 3,86/1.000 nascidos vivos, respectivamente; 44 casos foram relatados na capital do estado. Entre as mães de casos confirmados e descartados, a frequência de erupção cutânea durante a gravidez foi 50/97 (51,5%) e 8/51 (15,7%), respectivamente (p < 0,001); 33 casos confirmados (35,9%) apresentaram um escore z de perímetro cefálico entre -2 e -3, 23 (25%) entre -3 e -4 e 8 (8,7%) apresentaram escore z inferior a -4. As tomografias computadorizadas cerebrais revelaram calcificações em 78/95 (82,1%) dos casos. Lisencefalia, hidrocefalia e agenesia do corpo caloso também foram observadas com mais frequência. Os achados oftalmológicos incluíram rarefação e atrofia do epitélio pigmentar da retina. Foram observadas ausência de emissões otoacústicas em 21/70 casos. Um recém‐nascido também apresentou atrofia muscular dos membros inferiores. Não houve diferenças significativas nas taxas de vacinação para gripe, vacina difteria tétano e coqueluche acelular e hepatite B em qualquer grupo. Conclusões: O Estado do Piauí, como outros na região Nordeste, enfrentou, entre 2015 e 2016, uma epidemia de microcefalia congênita, supostamente relacionada à infecção congênita pelo vírus Zika, mais intensa na capital. Os desafios atuais incluem melhora do controle de vetores, pesquisa básica, ampliação de ferramentas de diagnóstico para exame pré‐natal do vírus Zika, vacinas e cuidados de saúde para crianças afetadas. Keywords: Microcephaly, Infants, Zika, State of Piauí, Palavras‐chave: Microcefalia, Neonatos, Zika, Estado do Piauí